2018
DOI: 10.1021/acs.chemrestox.7b00264
|View full text |Cite
|
Sign up to set email alerts
|

Influence of UGT2B10 Genotype on Urinary Excretion of 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanol-N-glucuronide by African American Smokers

Abstract: At similar smoking levels African American’s lung cancer risk is as much as twice that of whites. We hypothesized that racial/ethnic differences in UDP-glucuronosyltransferase (UGT)-catalyzed glucuronidation of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), a detoxication pathway for the tobacco-specific lung carcinogen NNK (4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone), may contribute to this variable risk. UGT2B10 catalyzes NNAL N-glucuronidation and a UGT2B10 splice variant is common among African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Alternatively, differences may reflect cigarette smoking behavior (e.g., puff number and maximum volume) as well as other individual factors (hormonal, genetics) that modify the cotinine pharmacokinetics parameters. Racial/ethnic differences in nicotine and cotinine glucuronidation (31,32), and to a lesser extent NNAL metabolism (33) have been noted in previous studies. In contrast, NNAL-CR concentrations were similar between NH Blacks and NH Whites.…”
Section: Discussionsupporting
confidence: 69%
“…Alternatively, differences may reflect cigarette smoking behavior (e.g., puff number and maximum volume) as well as other individual factors (hormonal, genetics) that modify the cotinine pharmacokinetics parameters. Racial/ethnic differences in nicotine and cotinine glucuronidation (31,32), and to a lesser extent NNAL metabolism (33) have been noted in previous studies. In contrast, NNAL-CR concentrations were similar between NH Blacks and NH Whites.…”
Section: Discussionsupporting
confidence: 69%
“…There are no changes in UGT plasticity (induction or suppression) in human hepatic tissue with smoking and alcohol consumption . Alterations of nicotine glucuronidation via UGT2B10 and UGT2B17 was found to be ethnicity‐dependent . Additionally, a study in HLM indicated potential competitive inhibition of morphine metabolism via UGT2B7 and UGT1A3 by alcohol, but this was not through altering enzyme expression per se …”
Section: Discussionmentioning
confidence: 96%
“…32,33 Alterations of nicotine glucuronidation via UGT2B10 and UGT2B17 was found to be ethnicity-dependent. 34,35 Additionally, a study in HLM indicated potential competitive inhibition of morphine metabolism via UGT2B7 and UGT1A3 by alcohol, but this was not through altering enzyme expression per se. 36 Our results did not demonstrate sex-related differences in the glucuronidation activity in HLMs using a large sample size in either adult or pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, polymorphisms in the nearest genes, i.e. UGT2B10 and 2B15 have been described to influence the glucuronidation rate of cotinine (nicotine metabolite) and postoperative anxiety after lorazepam premedication, respectively [13,14]. Furthermore, much interests have been paid to the UGT1A4*3 (142 T>G, L48V, MAF = 0.077) allele variant [15], which has been shown to alter the glucuronide formation of various compounds in vitro [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%